The Influence of Green Banking on Corporate Value in Commercial Banks in Indonesia - Fatmayanti, Fatmayanti; Waskito, Iman (East Asian Journal of Multidisciplinary Research, 2024)
The purpose of this study is to ascertain how Green Banking affects Corporate Value in Indonesian Commercial Banks. This study employs a descriptive methodology with a quantitative approach. Content analysis on Green Banking items based on the Green Banking Disclosure Index created by (Khan, Bose, Sheehy, & Quazi, 2021) was used to analyze the data. The Tobin's q ratio is used to calculate the worth of a company. In statistical testing, regression analysis techniques are applied. The study's findings indicate that green banking significantly reduces corporate value at Indonesian commercial banks. Green banking significantly affects how well a firm performs, particularly in terms of boosting public trust.